Reduction of phonetic mismatch negativity may depict illness course and predict functional outcomes in schizophrenia. (May 2021) - Mi, Lin; Wang, Le; Li, Xuanzi; She, Shenglin; Li, Haijing; Huang, Huiyan; Zhang, Jinfang; Liu, Yi; Zhao, Jingping; Ning, Yuping; Zheng, Yingjun
Abstract: Schizophrenia (SZ) is characterized by a series of cognitive impairments, including automatic processing impairment of basic auditory information, indexed by mismatch negativity (MMN). Existing studies mainly focus on MMN induced by deviant of single acoustic features, and relatively few studies have focused on complex acoustic stimuli, especially speech-induced MMN. Many cognitive impairments in SZ are related to speech function. Thus, the present study aimed to examine the reduction of phonetic MMN in SZ as a potential biomarker and its relationship with illness course and functional outcomes. Electroencephalogram (EEG) signals were recorded from 32 SZ and 32 healthy controls (HC) in a double oddball paradigm, with /da/ as the standard stimulus and /ba/ and /du/ as the deviant stimuli. MMN was computed for vowel and consonant deviants separately. Clinical symptoms were assessed using the Positive and Negative Symptom Rating Scale (PANSS). Illness duration and illness relapse were acquired by combining clinical interviews and electronic medical records. Functional outcomes were assessed using the Global Assessment of Functioning scale (GAF). Compared with HC, SZ showed lower amplitudes of phonetic MMN, especially for vowel deviants. In addition, the MMN amplitude of the vowel deviant was significantly correlated with illness duration, illness relapse, and functional outcomes among patients with SZ. These findings indicate that the pre-attentive automatic phonetic processing of SZ was impaired for both consonants and vowels, while the vowel processing deficit may be the key speech processing deficit in SZ, which could depict the illness course and predict the functional outcomes.